PENGARUH ATRAKSI, AMENITAS, DAN AKSESIBILITAS TERHADAP KEPUASAN PENGUNJUNG DI CAMPING GROUND GAYATRI CITEKO - Harry Wira Juliano; Hanifa Fahri; Prama Hardika; R.A Dhea Ayu; Fahrezzy Dwitama; Liliana Dewi (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
The purpose of this research is knowing the effect of attractions, amenities, Accessibility to Satisfaction Visitors Tourists in Camping Gayatri Citeko Ground. Inside approach This research is a quantitative approach with the survey method with distribute 50 questionnaires to 50 respondents. Researchers use Techniques data collection through interviews and questionnaire. While this research method in the form of variable operationalization. The results showed that Attraction variable has an effect on tourist interest. Attractions that is at Camping Ground Gayatri has attraction to tourists so that able to have an impact on interest tourist visitors. The accessibility consists of the availability of car transportation jeep, good road conditions can impact on interest tourist visitors. Amenity owned by the Gayatri Camping Ground which consisting of accommodation, rental camping tent, toilet, spot for Outbound, spot for jeeps, places worship, and Camping Ground guards able to have an impact on interest tourist visitors.